RESILIENCE AND MINDSET AS DRIVERS OF DIGITAL ADAPTATION OF FOOD BUSINESS MSMES IN GORONTALO CITY - Kaluku, Amelia; Alam, Heldy Vanni; Tantawi, Rezkiawan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to examine the role of resilience and mindset on adaptive behavior among MSME managers in facing digital transformation in the food business sector in Gorontalo City. This research uses a quantitative approach with a survey method. Data collection was conducted using a questionnaire, with a total sample of 54 respondents. The data analysis technique applied was multiple linear regression analysis. The results show that (1) resilience has a positive and significant effect on adaptive behavior, (2) mindset has a positive and significant effect on adaptive behavior, and (3) resilience and mindset simultaneously have a positive and significant effect on adaptive behavior. Descriptive findings based on business type indicate that the highest levels of resilience and adaptive behavior are found in restaurant businesses, while relatively lower levels are observed in bakery and pastry industries. Based on business duration, entrepreneurs who have operated longer tend to demonstrate better adaptive capabilities compared to newer businesses. This study recommends enhancing digital literacy training, strengthening entrepreneurial mindset, and providing business mentoring programs to improve the adaptive capacity of MSMEs in facing digital transformation.